2009
DOI: 10.1007/s12562-008-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of blue mussel extract in diets based on fish and soybean meals for tiger puffer Takifugu rubripes

Abstract: Inclusion of the water-soluble fraction of blue mussels Mytilus galloprovincialis as a feed additive was examined with tiger puffer Takifugu rupbripes. The control diet mainly consisted of fish meal, potato starch, and pollack liver oil. Experimental diets were formulated to replace 30% and 40% of the fish meal protein with defatted soybean meal (SBM), and were supplemented with 0-20% mussel extracts. Fish of 18 g initial body weight were fed each diet to satiation, twice daily, 6 days per week for 7 weeks at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Black sea turbot (Psetta maeotica) with an initial BW of 30.2 g can utilize up to 20% of defatted soybean meal with the supplementation of attractant (Yigit et al, 2010). Kikuchi and Furuta (2009) also demonstrated that tiger puffer (Takifugu rubripes) with an initial BW of 18g can accept 30-40% of defatted soybean meal diet with the inclusion of 10-20% of blue mussel extract. However, a study by Antolović et al (2012) showed that a smaller size of saddled bream juvenile (Oblada melanura) of initial BW 1.1 g was reported to be able to accept diet containing up to 28% of defatted soybean meal without any supplementation of essential amino acid.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Black sea turbot (Psetta maeotica) with an initial BW of 30.2 g can utilize up to 20% of defatted soybean meal with the supplementation of attractant (Yigit et al, 2010). Kikuchi and Furuta (2009) also demonstrated that tiger puffer (Takifugu rubripes) with an initial BW of 18g can accept 30-40% of defatted soybean meal diet with the inclusion of 10-20% of blue mussel extract. However, a study by Antolović et al (2012) showed that a smaller size of saddled bream juvenile (Oblada melanura) of initial BW 1.1 g was reported to be able to accept diet containing up to 28% of defatted soybean meal without any supplementation of essential amino acid.…”
Section: Discussionmentioning
confidence: 93%
“…(Bureau et al, 1998;Peres et al, 2003). Most of the carnivorous fish were recorded to be able to accept 10-40% of soybean meal (Tantikitti et al, 2005;Kikuchi & Furuta, 2009;Yigit et al, 2010;Lim et al, 2011;Yu et al, 2012;Antolović et al, 2012). However, some carnivorous and omnivorous fish such as European seabass, blue catfish and tilapia can accept up to 75-100% replacement by using soybean meal (Pantha, 1982;Webster et al, 1992;Kaushik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the blue mussel, their meals or extracts as natural feed attractant has been performed previously with contrary results (Kikuchi & Sakaguchi ; Kikuchi ; Kikuchi et al . ; Kikuchi & Furuta ,b). In this study, the inclusion of freeze‐dried mussel meal (2–8%) failed to increase DFI or SGR of fish fed by the RPC 50 diets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mussel meat and its extracts have been found to be efficient attractants in diets for Dover sole (Mackie et al . ), in diets based on FM protein and soy protein for Japanese flounder (Kikuchi ; Kikuchi, Ueda, Sugita & Takeda ) and tiger puffer ( Takifugu rubripes ) (Kikuchi & Furuta ,b). However, the issue whether freeze‐dried mussel meal could improve the palatability of alternative diets for juvenile turbot has not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, based on the data of FI, FBW, WG and SGR, it can be deduced that MM protein can substitute 50% of FM protein without a significant negative effect on growth of juvenile Ussuri catfish. The potential of MM as an alternative protein source for aquafeeds has been studied in some fish species (Kikuchi & Furuta, ; Kikuchi & Sakaguchi, ; Kyaw et al, ). Kyaw et al () reported that the optimal growth performance of juvenile tiger puffer ( Takifugu rubripes ) was observed when dietary MM inclusion level was at 53 g/kg compared with the other dietary treatments.…”
Section: Discussionmentioning
confidence: 99%